Pengenalan Alat Praktek Geografi Kepada Peserta Didik di Madrasah Aliyah Walisongo Kota Pontianak - Mustiah; Sariani, Novita; Norsidi; Suwarno, Agus (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The importance of introducing geographic practical tools such as GPS, stereoscopes and aerial photographs in schools for various reasons. Practical tools are tools that can be absorbed by the eyes and ears with the aim of helping educators to make the learning process more effective and efficient. The ones that will be used are GPS, stereoscopes and aerial photographs. The problem that occurs is not all schools can visit the laboratory of the geography education study program at Universitas PGRI Pontianak. This is because of time constraints due to the density of academic and non-academic activities and extra supervision in conducting visits outside the school environment. The method of community service with socialization activities for the introduction of practical tools that begin with theory then continue with direct practice using laboratory equipment. Presenting practical tools in real terms will provide variation in the learning process. Socialization activities are carried out in the school environment with time and participant agreements with the parties. Participants in the socialization activity are all students of class X of MA Walisongo, Pontianak City. The results obtained from the introduction of these geographic practical tools are: can increase students' abilities in using tools; provide variation in the learning process; ongoing cooperation between the geography education study program and the school.